Equivalence dominating sets in graphs - Arumugam S.; Sundarakannan M. (Utilitas Mathematica, 2013)
Let G =(V, E) be a graph. A subset S of V is called an equivalence set if every component of the induced subgraph(S) is complete. In this paper we introduce several parameters using equivalence sets and discuss their relation with other graph theoretic parameters.